The rational design, biofunctionalization and biological properties of orthopedic porous titanium implants: a review - Guo, Chunliang; Ding, Tao; Cheng, Yuan; Zheng, Jianqing; Fang, Xiule; Feng, Zhiyun (Frontiers in Bioengineering and Biotechnology, 2025)
Porous titanium implants are becoming an important tool in orthopedic clinical applications. This review provides a comprehensive survey of recent advances in porous titanium implants for orthopedic use. First, the review briefly describes the characteristics of bone and the design requirements of orthopedic implants. Subsequently, the pore size and structural design of porous titanium alloy materials are presented, then we introduce the application of porous titanium alloy implants in orthopedic clinical practice, including spine surgery, joint surgery, and the treatment of bone tumors. Following that, we describe the surface modifications applied to porous titanium implants to obtain better biological functions. Finally, we discuss incorporating environmental responsive mechanisms into porous titanium alloy materials to achieve additional functionalities.